Label-free optical interferometric microscopy to characterize morphodynamics in living plants - Ebrahimi, Samira; Moreno-Pescador, Guillermo; Persson, Staffan; Jauffred, Liselotte; Bendix, Poul Martin (Frontiers in Plant Science, 2023)
Fluorescence microscopy has played a pivotal role in an array of scientific discoveries during the last century. The success of fluorescence microscopy has prevailed despite several shortcomings related to limitations in measurement time, photobleaching, temporal resolution, and specific sample preparation. To bypass these obstacles, label-free interferometric methods have been developed which exploit the full wavefront information contained in light which has interacted with active and heterogeneously distributed biological material, e.g., optical height and intensity distribution. Here, we review some recent efforts in non-destructive imaging of plant cells and tissues using a few techniques in optical interferometry such as speckle imaging, optical coherence tomography and digital holography. These optical methods enable quantification of cell morphology and dynamic intracellular measurements over extended periods of time, demonstrating promising potential in the biomedical and life science fields. Recent investigations have showcased the potential of interferometric techniques for precise identification of seed viability and germination, plant diseases, plant growth and cell texture, intracellular activity and cytoplasmic transport. We envision that further developments of these label-free approaches, will open doors for long-lasting and high-resolution imaging of dynamic structures in plant biology ranging in size from sub-cellular to tissue scales